Use of nets treated with food-grade coatings on dry-cured ham to control Tyrophagus putrescentiae infestations without impacting sensory properties. (March 2018) - Campbell, Yan L.; Zhang, Xue; Shao, Wenjie; Williams, J.Byron; Kim, Taejo; Goddard, Jerome; Abbar, Salehe; Phillips, Thomas W.; Schilling, M.Wes
Abstract: Dry-cured hams may become infested with the ham mite Tyrophagus putrescentiae during aging. Food-grade coatings have been developed to control mite infestations as a potential alternative to replace methyl bromide, but dipping or spraying these coatings requires additional labor and processing steps. Nets composed of polyester, a polyester/cotton blend and cotton were infused with coatings that consisted of propylene glycol, and either propylene glycol alginate and carrageenan or xanthan gum. Results indicated that the polyester/cotton blend and cotton nets that contained propylene glycol were effective at controlling mite infestations in assays with ham cubes covered in nets. The polyester nets slowed mite growth but were not effective at controlling mite reproduction due to low absorbance of the coatings. Polyester/cotton blend nets treated with coatings on whole hams were not different from control hams with respect to flavor, texture and moistness. Mite infestation tests on whole hams indicated that coated nets with greater stitch densities were effective at controlling mite growth. Future research will include the optimization of coating formulations and scaled-up testing in dry-cured ham plants. Highlights: Polyester/cotton blend and cotton nets treated with food grade coatings controlled mite infestations. Using nets treated with coatings to age whole hams did not cause sensory differences. Nets of high-stitch density with coatings inhibited mite reproductions on whole hams.